1995
DOI: 10.1111/j.1651-2227.1995.tb13621.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast milk β‐glucuronidase and prolonged jaundice in the neonate

Abstract: Breast milk samples from mothers of breast‐fed, healthy, term newborns with unexplained prolonged jaundice were analyzed for β‐glucuronidase activity. Mean enzyme activity was 75.7 ± 34.5 modified Sigma units/ml in the breast milk samples ingested by the study group of jaundiced babies (n= 25) and 82.2 ± 40.1 modified Sigma units/ml in the samples ingested by the control group of non‐jaundiced babies (n = 20) (p > 0.05). Enzyme activities at 2, 3 and 4 postnatal weeks were 101.0 ±39.9, 66.0 ± 20.7 and 57.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 20 publications
1
28
1
1
Order By: Relevance
“…In 1986 some authors suggested that ß-glucuronidase was an important factor in the pathogenesis of jaundice in breast-fed babies [4]. But these results were not confirmed by other studies [5,6].…”
contrasting
confidence: 51%
See 1 more Smart Citation
“…In 1986 some authors suggested that ß-glucuronidase was an important factor in the pathogenesis of jaundice in breast-fed babies [4]. But these results were not confirmed by other studies [5,6].…”
contrasting
confidence: 51%
“…Sirota et al [5] found higher concentrations of ß-glucuronidase in the breast milk of diabetic mothers in comparison to nondiabetic ones. However, Ince et al [6] and, recently, Erdem et al [7] did not confirm these results. In our study, we did not find significantly higher concentrations of ß-glucuronidase in breast milk of mothers with jaundiced babies in comparison to controls.…”
Section: Discussionmentioning
confidence: 43%
“…However, one of the problems associated with the use of the bacterial gus gene as a reporter is the presence of 'endogenous GUS' activity in some species. Endogenous GUS activity has been reported in various organisms including: 1 -bacterial species, such as the enterobacterium E. coli and Shigella, nonenterobacterial such as Bacteroides and Clostridium (Hawkesworth et al, 1971), Streptococcus, Staphylococcus, Corynebacterium (Levvy and Marsh, 1959), Alcaligenes (Jefferson, 1989) and many soil bacteria (Ritz et al, 1994); 2 -Some tissues of vertebrates such as kidney, liver and spleen (Kyle et al, 1992), human breast milk (Alonso et al, 1991;Ince et al, 1995); 3 -Invertebrates such as snails (Levvy and Marsh, 1959), nematodes (Jefferson, 1985;Sebastiano et al, 1986) and insects (Langley et al, 1983;Levvy and Marsh, 1959), housefly (Musca domestica) and various locusts (Levvy and Marsh, 1959) and 4 -Plant species. In plants, endogenous GUS activity was first described in Arabidopsis by Jefferson et al (1987).…”
Section: Introductionmentioning
confidence: 97%
“…The mechanism of breast milk jaundice is not clearly understood yet. A number of theories have arisen to explain it, including environmental and genetic factors [59]. To date, a correlation between maternal diet and breast milk jaundice has not been verified.…”
Section: Introductionmentioning
confidence: 99%